Pola Asuh Orang Tua Mempengaruhi Prestasi Belajar Anak Tunagrahita - Zulhaini Sartika A. Pulungan; Edi Purnomo; Nur Adhilah Baharuddin (Jurnal Kesehatan Manarang, 2019)
Mental retardation have less school performance, intelligence quotient (IQ) below 70, dependence on others, lack responsiveness, lack proportional physical appearance, late speech development and limited language. This study aims determine the influence of parenting on learning achievement of mental retardation in SDLB Negeri Pembina West Sulawesi Province. This research use descriptive corelational with cross sectional design. Population of all parents and children with special needs in SDLB Negeri Pembina. Research subjects were taken by purposive sampling, after given informed consent and fulfilled inclusion criteria: children with mild mental retardation, still active school, parents and children live at home. Research subjects 20 people. Duration of one week's data retrieval. Data analysis was done by descriptive analysis by showing percentage of each variable. Fisher's exact test was conducted to determine the effect of parenting on learning achievement of mental retardation, with 95% confidence level (Î± 0,05). Parenting affecting learning achievement of mental retardation in SDLB Negeri Pembina West Sulawesi Province with p value = 0,022. The most effective parenting pattern to apply is democratic parenting, because the pattern of parenting runs in accordance with the growth and development of children, so as to improve the learning achievement of children. Democratic parenting style emphasizes the educational or educational aspect in guiding the child so that parents often give more understanding, explanation, and reasoning to help the child understand why the behavior is expected. Parenting influences the learning achievement of mental retardation in SDLB Negeri Pembina West Sulawesi Province.